Simulation of optical spatial solition - Shi, Yuefei. (2008)
Optical soliton refers to the short laser pulses propagating in certain kinds of nonlinear media. The dispersion and self-phase modulation caused by Kerr nonlinearity cancel each other, so short laser pulses can propagate without changing their shapes over time, and interact as new dynamic entities.